Genotype-dependent response of soybean (Glycine max L.) to the vermicompost application in the lowland agroecosystem - Naja Ananda Putri; Nilahayati Nilahayati; A. G. Rosnina (Faculty of Agriculture, Universitas Malikussaleh, 2026)
Soybean (Glycine max L.) productivity in Indonesia remains insufficient to meet national demand, necessitating improvements in both genetic potential and nutrient management strategies. This study aimed to evaluate the growth and yield performance of four soybean genotypes under different vermicompost doses in lowland agroecosystems. The experiment was conducted in Paloh Lada Village, Dewantara District, North Aceh, using a factorial randomized block design with two factors: four soybean genotypes (Anjasmoro, Dena 1, Denasa 2, and M.1.1.3 line) and three vermicompost doses (0, 5, and 10 t ha⁻¹). Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test at 5% significance level. Results showed that genotype significantly affected all observed variables except leaf area. The M.1.1.3 line consistently produced the highest yield (up to 4.12 t ha⁻¹, compared with 10 t ha⁻¹ vermicompost). Vermicompost application significantly increased plant height, root nodules, filled pods, seed weight per plant, seed weight per plot, and yield. Significant genotype × vermicompost interactions were observed for plant height, nodulation, seed weight, and yield. The optimal dose was 10 t ha⁻¹. These findings demonstrate that integrating responsive genotypes with appropriate organic fertilization enhances soybean productivity in lowland environments.